(untitled) (Bioagro, 2026)
Urban gardens offer an alternative way to obtain food; they also promote environmental stewardship and social cohesion; however, it is essential to use substrates that are suitable for plant growth and to increase production. The bacteria present in a crop’s growing medium largely determine the success of the harvest; therefore, the objective of this study was to characterize the bacterial community of different growing media used in urban gardens. Four substrates were analyzed: peat moss, due to its widespread use in gardens and orchards; black soil (from a nursery); agricultural soil (from northern Tamaulipas, Mexico); and a mixture of agricultural soil with worm castings and mycorrhizae. Genomic DNA was extracted from all substrates and the 16S region was amplified; the sequences were analyzed using the 16S Metagenomics application. The most prevalent phyla were found to be Actinobacteria, Proteobacteria, and Firmicutes; and among the genera, Bacillus, Solirubrobacter, Rubrobacter, and Streptomyces stood out. All these microorganisms have been linked to benefits for crops, so their presence could promote the growth of various plant species cultivated in urban gardens.